Mapping the Brain: Resources for Researchers in Neurosciences. - Victoria Shelton (Issues in Science and Technology Librarianship)
The article provides information on selected Web-based resources for researchers in neuroscience and is primarily intended for librarians who assist neuroscientists engaged in research. The inclusion of resources was based on criteria stated in this article. These resources include: Web sites for neuroscientists; digital journal archives; and directories, databases, and search engines.